Hole mobility of 3.56 cm2 V−1 s−1 accomplished using more extended dithienothiophene with furan flanked diketopyrrolopyrrole polymer1. Issue 36 (28th September 2015) - Sonar, Prashant; Chang, Jingjing; Shi, Zugui; Gann, Eliot; Li, Jun; Wu, Jishan; McNeill, Christopher R.
<x xml:space="preserve">Abstract</x> A highly extended dithienothiophene comonomer building block was used in combination with highly fused aromatic furan substituted diketopyrrolopyrrole for the synthesis of novel donor–acceptor alternating copolymer PDPPF-DTT.